Educational Outcomes of Students Living in Remote Reserve Communities: Complex and Multifaceted Indigenous Poverty - Anderson, Kristen; Azam, Saiqa (Critical Education, 2025)
Poverty impacts the mental, physical, social and emotional health and wellbeing of individuals, particularly Indigenous children and adolescents living in remote reserve communities. Within many diverse ways to conceptualize poverty, Indigenous poverty stems from the detrimental traumas resulting from colonialism, continued systemic racialization, removal of cultural identity and loss of self-determination. Residential schools and other colonial policies and traumas have eroded Indigenous culture, language and ways of life. Ongoing systemic and environmental racism, discrimination and stereotyping lend to the continued cycle of poverty for Indigenous people living in Canada, with those living on reserve experiencing the most extreme effects on their life and academic success. This article reviews the literature to draw attention to the impacts of complex and multifaceted Indigenous poverty on educational outcomes for those Indigenous students living on reserve. Overall, students who experience poverty experience negative impacts on their physical, mental, cognitive and emotional development, functioning and processing, resulting in lower educational and academic outcomes and a more likely chance that they will continue to experience poverty as adults. In the context of Indigenous ways of being, living in poverty can cause a disconnection from the land, culture and identity so integral to their being.